Sustained Infiltration of Neutrophils Into the CNS Results in Increased Demyelination in a Viral-Induced Model of Multiple Sclerosis - Skinner, Dominic D.; Syage, Amber R.; Olivarria, Gema M.; Stone, Colleen; Hoglin, Bailey; Lane, Thomas E. (Frontiers in Immunology, 2022)
Intracranial inoculation of the neuroadapted JHM strain of mouse hepatitis virus (JHMV) into susceptible strains of mice results in acute encephalomyelitis and chronic immune-mediated demyelination similar to the human demyelinating disease multiple sclerosis (MS). JHMV infection of transgenic mice in which expression of the neutrophil chemoattractant chemokine CXCL1 is under the control of a tetracycline-inducible promoter active within GFAP-positive cells results in sustained neutrophil infiltration in the central nervous system (CNS) that correlates with an increase in spinal cord demyelination. We used single cell RNA sequencing (scRNAseq) and flow cytometry to characterize molecular and cellular changes within the CNS associated with increased demyelination in transgenic mice compared to control animals. These approaches revealed the presence of activated neutrophils as determined by increased expression of mRNA transcripts associated with increased neutrophil effector functions, such as CD63, MMP9, S100a8, S100a9, and ASPRV1, as well as by altered neutrophil morphology and protein expression. Collectively, these findings reveal insight into changes in the profile of neutrophils associated with increased white matter damage in mice persistently infected with a neurotropic coronavirus.